The Effects of the Remanining Time of Anterior Nasal Packing in Nasal Passage on Healing After Septal Surgery - Çetinkaya, Tufan (Fırat University, 2001)
One of the most disturbing problems to the patient after septal surgery is the presence of nasal packing. Postoperative nasal packing use has some advantages and disadvantages. This study was performed to determine whether there's a relation between the duration of postoperative nasal packing and patient complaints. A total of 66 patients undergoing septoplasty or septorhinoplasty were included into the study. The patients were divided into two groups according to the duration of nasal packing. The packings in the first group was left in place for 48 hours and for 72 hours in the second group. During this time, the patients were evaluated for the presence of postoperative bleeding, pain, restlessness, oedema, septal haematoma, the need a new packing and evaluated postoperatively at the first month for nasal obstruction, septal perforation, crusting, synechia and heavy nasal secretion. Until the removal of the packings the restlessness was assessed. This parameter showed statistically significant increase in the second group (P0.05). With these findings, we concluded that the removal of nasal packing as early as possible in the postoperative period should be the choice of procedure.

Septal cerrahi sonrası hastayı en çok rahatsız eden durumlardan biri nazal tamponların varlığıdır. Postoperatif nazal tampon uygulamasının bazı avantaj ve dezavantajları vardır. Bu çalışma postoperatif nazal tampon uygulama süresiyle hastanın bulgu ve şikayetleri arasında ilişki olup olmadığının saptanması amacıyla yapıldı. Çalışmaya septoplasti veya septorinoplasti yapılıp nazal tampon uygulanan 66 hasta alındı. Hastalar tamponların kalış süresine göre iki gruba ayrıldı. Birinci grupta tamponlar 48 saat, ikinci grupta 72 saat tutuldu. Bu sırada hastalar postoperatif kanama, ağrı, rahatsızlık hissi, ödem; yeniden tampon gereksinimi, septal hematom ve postoperatif birinci aydan sonra nazal obstrüksiyon, septal perforasyon, kurutlanma, sinesi ve aşırı nazal sekresyon açısından değerlendirildi. Tamponların boşaltılmasına kadar geçen sürede ikinci grupta rahatsızlık hissi açısından birinci gruba göre istatistiksel olarak anlamlı bir fark saptandı (P0.05). Bu bulgularla postoperatif nazal tamponları mümkün olduğunca kısa sürede boşaltmanın tercih edilmesi gereken bir uygulama olacağı düşüncesindeyiz.
SEPTAL CERRAHİ SONRASI UYGULANAN ANTERİOR NAZAL TAMPONUN NAZAL PASAJDA KALIŞ SÜRESİNİN İYİLEŞME ÜZERİNE ETKİLERİ